The Challenge for Nursing Administrators in Human Resource Management: Generation Z Professional Nurses’ Group - Wongkanghae, Supitcha; Mongkholkham, Chuthathip (NU Journal of Nursing and Health Sciences, 2023)
This article aims to present an idea of human resource management in generation Z nurses which emphasizes response to their needs and work expectations. This article also suggests guidelines for the generation Z nurse administrator which include 5 main topics: 1) Job design: considering work design for generation Z which consists of autonomy, skill variety, task identity, task significance, and feedback. 2) Human resource development: encouraging professional development 3) Participation: listening, respecting others' ideas, and creating good communication in the workplace 4) Shared values in the workplace: social and altruistic work values, moral and ethical work values 5) Performance management and compensation: performance evaluation and providing fringe benefits or rewards. This guideline would be beneficial for administrators to enhance motivation and job retention of generation Z nurses in nursing organizations. Also, the guideline can be applied for being conceptual frameworks of studies in terms of future research development.